Extracción de polifenoles de plantas silvestres de zarzamora (Rubus spp.) para aplicaciones antimicrobianas - Silva Adame, María Blanca (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The Rubus genus presents plants as the blackberry and raspberry that develop in several States of the Mexican Republic, between which Michoacán's condition stands out, where there have been described species considered as valuable resources of economic importance. The fruits of the wild blackberry represent an alternate source for the familiar revenue in the communities where they develop, whereas the stems and leaves are in use in the traditional herbolaria thanks to the presence of compounds with antimicrobial activity against phytopathogens, emphasizing Botrytis cinerea, Alternaria alternata, Fusarium sp., Pseudomonas spp. Nevertheless they are more than 700 Rubus's species in the world, only has evaluated the antimicrobial potential of a small number, which is why the importance of evaluating the potential of more than 20 Rubus's Mexican species is explaned. Among the principal compounds with antimicrobial activity there are polyphenols; these are extensively distributed in diverse organs of the plants: flowers, fruits, leaves, etc., since they operate as protective substances against the radiation UV, and as mechanisms of defense. In human beings, the polyphenols possess charitable effects on the health, acting like powerful antirust and intervening in the prevention of degenerative diseases of chronic type. Nowadays, there are small the studies that have been done on the presence and content of compounds bioactivos in Rubus's wild species in Michoacán; in this context, the present the present project tries to extract polyphenolic compounds from different organs of the plant for the evaluation of his microbicide capacity generating evidences on of their possible applications for biological control. Here we evaluated three materials of wild blackberry, Rubus adenotrichos, Rubus coriifolius and morfoespecies "Waxen", preparing extracts of leaves and stems. The best result of antimicrobial activity was registered by the methanolic extract of stem of Rubus adenotrichos that reached 97.78 % of inhibition of the growth of Pantoea stewartii, percentage reflected by the reduction of the UFC/mL in a logarithmic unit. This allows to propose to the evaluated plants as sources of natural compounds for biological control of microorganism.

El género Rubus presenta plantas como la zarzamora y frambuesa que se desarrollan en varios Estados de la República Mexicana, entre los que destaca el estado de Michoacán, donde se han descrito especies consideradas como valiosos recursos de importancia económica. Los frutos de la zarzamora silvestre representan una fuente alterna para el ingreso familiar en las comunidades donde se desarrollan, mientras que los tallos y hojas se utilizan en la herbolaria tradicional gracias a la presencia de compuestos con actividad antimicrobiana contra fitopatógenos, destacando Botrytis cinerea, Alternaria alternata, Fusarium sp., Pseudomonas spp. No obstante lo anterior, de las más de 700 especies de Rubus que se reportan en el mundo, sólo se ha evaluado el potencial antimicrobiano de un pequeño número ellas, de ahí la importancia de evaluar el potencial de las más de 20 especies mexicanas de Rubus. Dentro de los principales compuestos reportados con actividad antimicrobiana se encuentran los polifenoles; éstos están extensamente distribuidos en diversos órganos de las plantas: flores, frutos, hojas, etc., ya que actúan como sustancias protectoras contra la radiación UV, como atrayentes de polinizadores y como mecanismos de defensa. En humanos, los polifenoles poseen efectos benéficos sobre la salud, actuando como potentes antioxidantes e interviniendo en la prevención de enfermedades de tipo crónico degenerativas. Actualmente, son pocos los estudios que se han hecho sobre la presencia y contenido de compuestos bioactivos en especies silvestres de Rubus en Michoacán; en este contexto, el presente proyecto pretende extraer compuestos polifenólicos a partir de distintos órganos de la planta para la evaluación de su capacidad microbicida generando evidencias sobre los compuestos involucrados en la herbolaria regional y sus posibles aplicaciones para el control biológico de fitopatógenos.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FAPJ-M-2014-1516; Bioactividad; Metabolitos secundarios; Fitopatógenos; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2052